2012
DOI: 10.1016/j.jaci.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Relating small airways to asthma control by using impulse oscillometry in children

Abstract: Background Previous reports suggest that peripheral airways are associated with asthma control. Patient history, although subjective is used largely to assess asthma control in children because spirometry is many times normal. Impulse oscillometry (IOS) is an objective non-invasive measurement of lung function, which has the potential to examine independently both small and large airway obstruction. Objective To determine the utility of IOS in assessing asthma control in children. Methods Asthmatic and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
196
4
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(225 citation statements)
references
References 47 publications
14
196
4
11
Order By: Relevance
“…The IOS results at age 16 years revealed significantly higher estimated medians for R 5 , R [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , and AX 0.5 in moderate to late preterm male subjects compared with term male subjects ( Table 2). Although a similar trend was seen for female subjects, a significant difference was recorded only for R 5 .…”
Section: Lung Function After Moderate To Late Preterm Birthmentioning
confidence: 95%
See 2 more Smart Citations
“…The IOS results at age 16 years revealed significantly higher estimated medians for R 5 , R [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , and AX 0.5 in moderate to late preterm male subjects compared with term male subjects ( Table 2). Although a similar trend was seen for female subjects, a significant difference was recorded only for R 5 .…”
Section: Lung Function After Moderate To Late Preterm Birthmentioning
confidence: 95%
“…Quality control was performed at the time of examination by visual inspection of the waveforms. Given that coherence, which is a measure of testing reliability, was >0.80 at 10 Hz, the mean value of resistance at 5 Hz (R 5 ), resistance at 20 Hz (R 20 ), frequency dependence of resistance (ie, R [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and reactance area (AX) were used for analysis. AX may boost the assessed response inappropriately compared with the R 5-20 response because it multiplies 2 partly independent reactions of the airways.…”
Section: Measurements Of Lung Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al [25] demonstrated that increased peripheral airway indexes of FOT, including R5-R20 and ALX, predict asthma exacerbation. We thus asked whether salivary SP-D levels were associated with the severity of an acute asthma attack, as assessed by AAIRS [22].…”
Section: Salivary Sp-d Concentrations Increased During Acute Asthma Amentioning
confidence: 99%
“…It measures both small and large airways resistance and resonance capacitance of the lung [11]. Due to detecting large and small airways diseases separately, IOS has been applied in asthma diagnosis and management [12][13][14].…”
Section: Introductionmentioning
confidence: 99%